The monkey wrench gang - Abbey, Edward 1927-1989 (HarperPerennial, 2006)
In the author's classic novel of environmental activism, four rebels declare war on stripminers, clear-cutters, and othe destroyers of the environment and raiders of natural resources
Originally published: Philadelphia : Lippincott, 1975. With additional material. - Includes final section called "P.S.: Insights, interviews & more.". - Continued by: Hayduke lives!
Keywords: Environmentalists / Southwestern States / Fiction; Deep ecology / Southwestern States / Fiction; Environmental protection / Fiction; Umweltschutz; Arizona, Northern / Fiction; Utah / Fiction; Southwestern States / Fiction; Fiktionale Darstellung